Zinc Oxide Nanoparticles Prepared By a Simple Heating: Effect of Polymer Addition and Polymer Absence on the Morphology - Abdullah, Mikrajuddin; Okuyama, Kikuo (Journal of Engineering and Technological Sciences, 2004)
Zinc oxide (ZnO) nanoparticles were prepared by a simple heating of precursors in a furnace at temperatures of below 1000°C in an air environment. If zinc nitrate was used as precursor, polymer (e.g., polyethylene glycol (PEG)) must be added into the precursor to produce ZnO in nanometer size. The absence of polymer led to the presence of several micrometer-sized flakes. In addition, the heating temperatures must be higher than 500°C to completely decompose the organic material in final product. However, if zinc acetate was used as precursor, nanometer-sized ZnO having a high crystallinity can be obtained even when the polymer was absent. Interestingly, we also found that heating at low temperatures (e.g. 400°C) resulted in ZnO nanorods with an elongation ratio of around 5. This method is rapid, economically efficient, and readily scalable for industrial applications.